Heat shock proteins in the context of photodynamic therapy: Autophagy, apoptosis and immunogenic cell death - Rodriguez, Matias Exequiel (2016)
Photodynamic therapy (PDT) is an anti-tumor treatment administered for the elimination of early-stage malignancies and the palliation of symptoms in patients with late-stage tumors, which involves the activation of a photosensitizer (PS) using light of a specific wavelength, which also generates singlet oxygen and other reactive oxygen species (ROS) that cause tumor cell death. Several mechanisms are involved in the protective responses to PDT including the expression of chaperone/heat shock proteins (HSPs). The HSPs are a family of proteins that are induced by cells in response to exposure to stressful conditions. In the last few decades, it has been discovered that HSPs can play an important role in cell survival, due to the fact that they are responsible for many cytoprotective mechanisms. These proteins have different functions depending on their intracellular or extracellular location. In general, intracellular HSPs have been related to an anti-apoptotic function and recently, HSP-induced autophagy has shown to have a protective role in these chaperones. In contrast, extracellular HSPs or membrane-bound HSPs mediate immunological functions. In the present article, we attempt to review the current knowledge concerning the role of HSPs in the outcome of PDT in relation to autophagy and apoptosis mediated-resistance to photodynamic treatment. We will also discuss how certain PDT protocols optimally stimulate the immune system through HSPs.